2002
DOI: 10.1073/pnas.232580399
|View full text |Cite
|
Sign up to set email alerts
|

A cell-free protein synthesis system for high-throughput proteomics

Abstract: We report a cell-free system for the high-throughput synthesis and screening of gene products. The system, based on the eukaryotic translation apparatus of wheat seeds, has significant advantages over other commonly used cell-free expression systems. To maximize the yield and throughput of the system, we optimized the mRNA UTRs, designed an expression vector for large-scale protein production, and developed a new strategy to construct PCRgenerated DNAs for high-throughput production of many proteins in paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
386
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 466 publications
(399 citation statements)
references
References 30 publications
12
386
0
1
Order By: Relevance
“…ORFs of human E3 ubiquitin ligases were amplified from a set of National Institutes of Health mammalian gene correction clones by PCR using target protein-specific sense primers beginning with the S1 sequence and the antisense primers AODA2306 (for pBluescriptR-based clones (27)) or pDONR221_ 1 st A4080 (5Ј-ATCTTTTCTACGGGGTCTGA-3Ј for pCMV-SPORT6, pOTB7, pCR4-TOPO, and pCR-BluntII-TOPObased clones). A second split-primer PCR was carried out using an SPu sense primer containing an SP6 promoter sequence, a deSP6E01 sense primer containing a GST tag sequence (28), and the respective AODA2303 (for AODA2306 (27)) or pDO-NR221_2 nd A4035 (5Ј-ACGTTAAGGGATTTTGGTCA-3Ј for pDONR221_1 st A4080) antisense primer. Expression of GSTtagged recombinant proteins was performed on 96-well plates using the GenDecoder 1000 protein synthesizer (CellFree Sciences, Japan) according to the protocol of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ORFs of human E3 ubiquitin ligases were amplified from a set of National Institutes of Health mammalian gene correction clones by PCR using target protein-specific sense primers beginning with the S1 sequence and the antisense primers AODA2306 (for pBluescriptR-based clones (27)) or pDONR221_ 1 st A4080 (5Ј-ATCTTTTCTACGGGGTCTGA-3Ј for pCMV-SPORT6, pOTB7, pCR4-TOPO, and pCR-BluntII-TOPObased clones). A second split-primer PCR was carried out using an SPu sense primer containing an SP6 promoter sequence, a deSP6E01 sense primer containing a GST tag sequence (28), and the respective AODA2303 (for AODA2306 (27)) or pDO-NR221_2 nd A4035 (5Ј-ACGTTAAGGGATTTTGGTCA-3Ј for pDONR221_1 st A4080) antisense primer. Expression of GSTtagged recombinant proteins was performed on 96-well plates using the GenDecoder 1000 protein synthesizer (CellFree Sciences, Japan) according to the protocol of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…This eukaryotic cellbased in vitro translation method offers several advantages over the E. coli system, particularly allowing the high-throughput expression of recombinant proteins from cloned ORF resources in vitro (18,19). In this study, to generate the protein library, template DNAs containing an ORF were amplified from a collection of National Institutes of Health mammalian gene correction clones encoding 96 RING finger-type E3 ubiquitin ligases and fused with a 5Ј terminal SP6 promoter and GST tag sequences by split primer PCR (28,39). Agarose gel electrophoresis and ethidium bromide staining of the split PCR product confirmed that 92 DNA templates were synthesized successfully (supplemental Fig.…”
Section: Screen For Human E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…30 The recombinant NbAC was synthesized by a robotic protein synthesizer, Protemist ® DT (CellFree Sciences) according to the manufacturer's instructions.…”
Section: Sequencingmentioning
confidence: 99%
“…Yeast Trm8-Trm82 heterodimer was synthesized by a wheat germ in vitro translation system [25][26][27][28]. Because there was a 6 · His tag sequence expressed at the N-terminus of Trm82, the synthesized enzyme could be purified by Ni-NTA superflow column chromatography and DE52 column chromatography [28].…”
Section: Preparation Of Yeast Trna (M 7 G46) Methyltransferasementioning
confidence: 99%